2011
DOI: 10.5336/medsci.2010-20548
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preoperative Oral Carbohydrate Loading on Stress Response in Patients Undergoing Major or Minor Surgery

Abstract: Ö ÖZ ZE ET T A Am ma aç ç: : Bu ça lış ma nın ama cı, ma jör ve mi nör cer ra hi ge çi ren has ta lar da pre o pe ra tif oral karbonhidrat yük le me si nin aç lık, su suz luk, ağız ku ru lu ğu, hal siz lik his si, bu lan tı-kus ma, stres cevap, ba ğır sak ha re ket le ri ve ta bur cu luk sü re si üze ri ne et ki si ni araş tır mak tır. G Ge e r re eç ç v ve e Y Yö ön n t te em m l le er r: : Doksan has ta ma jör ve mi nör cer ra hi ola rak iki gru ba (n= 45), her grup da ken di için de ça lış ma (Ç), pla se bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
(54 reference statements)
1
7
0
2
Order By: Relevance
“…summarizes the network of direct evidence available for this outcome. This was reported by 25 studies involving 1888 participants. Mean length of postoperative stay in the included studies ranged from 1 to 17 days.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…summarizes the network of direct evidence available for this outcome. This was reported by 25 studies involving 1888 participants. Mean length of postoperative stay in the included studies ranged from 1 to 17 days.…”
Section: Resultsmentioning
confidence: 65%
“…summarizes the database search and study selection process. Forty‐three RCTs, involving 3110 patients, fulfilled the inclusion criteria. One trial could not be included in the multiple‐treatments meta‐analysis as the only relevant reported outcome was the aspiration pneumonitis rate, which was zero across all groups in all RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…Preoperatif açlık hissinin Grup I'de %61, Grup II'de %80 oranında; susuzluk hissinin Grup I'de %63,4, Grup II'de %77,1 gibi yüksek oranlarda gö-rülüyor olması, Özdemir ve ark.nın yaptığı çalış-manın sonuçlarıyla 3 paralel olarak uzun süren açlık ve susuzluk sürelerinin hasta konforunu bozduğunu göstermektedir. Benzer bir çalışmada, düşük riskli hastalara ameliyattan 2 saat öncesinde oral rehidratasyon sıvısı verilmesinin hastaların preoperatif dönemde duyduğu açlık ve susuzluk hissini azaltan, güvenli bir yöntem olduğu gösterilmiştir.…”
Section: Discussionunclassified
“…Uzamış açlık ve susuzluğun yol açtığı metabolik bozuklukların ve diğer komplikasyonların önüne geçmek için oral rehidratasyon sıvılarının (ORS) ameliyat önce-sinde 2 saate kadar kullanımının güvenli ve etkili olduğu birçok çalışmayla gösterilmiştir. [3][4][5][6] Preoperatif hazırlık klavuzları da açlık ve susuzluğun sebep olduğu komplikasyonların önlenmesi için ameliyat öncesi 2 saate kadar berrak sıvı veya oral rehidratasyon sıvılarının alınmasını önermektedir.…”
Section: Laparoskopik Kolesistektomi Yapılacak Sağlıklı Erişkinlerdeunclassified
“…Previous studies proved bene ts of preoperative carbohydrate loading, which not only improved perioperative well-being but also decreased insulin resistance after elective surgery (Bilku, et al, 2014; Awad, et al, 2013). Some studies also reported that preoperative oral carbohydrate promoted the recovery of gastrointestinal function (ÖZdemİR, et al, 2011; and shortened the length of hospital stay without increasing the risk of aspiration (Gianotti, et al, 2018;Smith, et al, 2014). Several guidelines recommend that carbohydrate drinks should be allowed in patients without diabetes undergoing elective surgery until 2 hours before initiating anesthesia (Gustafsson, et al, 2018;Feldheiser, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%